Impact of Patient–Doctor Race Concordance on Rates of Weight-Related Counseling in Visits by Black and White Obese Individuals - Bleich, Sara N. (2011)
The objective of this study was to assess the impact of patient-provider race concordance on weight-related counseling among visits by obese patients. We hypothesized that race concordance would be positively associated with weight-related counseling. We used clinical encounter data obtained from the 2005–2007 National Ambulatory Medical Care Surveys (NAMCS). The sample size included 2,231 visits of black and white obese individuals (ages 20 and older) to their black and white physicians from the specialties of general/family practice and general internal medicine. Three outcome measures of weight-related counseling were explored: weight reduction, diet/nutrition, and exercise. Logistic regression was used to model the outcome variables of interest. Wald tests were used to statistically compare whether physicians of each race provided counseling at different rates for obese patients of different races. We did not observe a positive association between patient–physician race concordance and weight-related counseling. We found that visits by black obese patients to white doctors had a lower odds of exercise counseling as compared to visits by white obese patients to white doctors (odds ratio (OR) = 0.54; 95% confidence interval (CI): 0.31, 0.95), and visits by black obese patients to black physicians had lower odds of receiving weight-reduction counseling than visits among white obese patients seeing black physicians (OR = 0.34; 95% CI: 0.13, 0.90). Black obese patients receive less exercise counseling than white obese patients in visits to white physicians and may be less likely than white obese patients to receive weight-reduction counseling in visits to black physicians.